Perennial Garden Color - Welch, William C. (William Carlisle), 1939- (Book collections on Project MUSE., 2013)
Gardeners in Texas and the South face their own special problems with climate and growing seasons, and they need a guide written specifically for the region in order to have the greatest chance of success. William C. Welch's Perennial Garden Color directly fills this need, and for years gardeners have relied on this book to aid their efforts to beautify their outdoor spaces. Now in a new Texas A & M University Press edition, this time-tested classic, dubbed a "masterpiece" by Neil Sperry, is available again. Lavishly illustrated with more than five hundred breat.